ANALISIS PRAGMATIK WAR KNETZ VS SEABLINGS DI PLATFORM X - Kuswara, Dewi; Puspitarini, Herning; Putri, Dira Shafira; Ashari, Naila; Syahirah, Rania; Mikradi, Wahyu (STKIP Subang, 2026)
The phenomenon of communication conflict on social media is increasingly rising, one example being the conflict between Knetz and SEAblings on the X platform, which was triggered by an incident at a DAY6 concert in Kuala Lumpur. This conflict developed into a debate characterized by utterances containing satire, mockery, and even insults related to group identity and stereotypes. This study aims to analyze the forms and meanings of utterances within the conflict and to identify the contributing factors through a pragmatic approach. The method used involves data collection techniques such as observation and documentation of posts, comments, and screenshots of interactions on the X platform. The data were then analyzed based on the concepts of speech acts, implicature, and the cooperative principle in pragmatics. The results show that the utterances produced contain non-literal meanings such as satire, sarcasm, and insults. The conflict is influenced by differences in group identity, the use of linguistic stereotypes, fanwar dynamics, and anonymity in online communication. In this context, language functions not only as a tool of communication but also as a means of expressing identity and social conflict. Keyword: Pragmatics, Knetz, SEAblings